"Growing out of depression and neuroticism": Keep children away from maltreatment. (May 2022) - Wang, Xiaoyue; Xie, Ruibo; Ding, Wan; Jiang, Min; Li, Weijian
Highlights: ·This article adopts a person-centered perspective, focusing on the heterogeneity among children that previous variable-centered studies have ignored. ·The development of depression and neuroticism in children is not independent and is closely related. Most children who present with high levels of depression or neuroticism are likely to be concomitant with high levels of neuroticism or depression at the same time. ·All types of maltreatment can have an impact on the independent or combined developmental trajectory of depression and neuroticism in children. After experiencing maltreatment, a small proportion of children will show a developmental pattern of decreased depression but increased neuroticism. Abstract: This study aimed to examine the independent and joint developmental trajectories of depression and neuroticism in children. The relationship between different types of maltreatment and the heterogeneity of their developmental trajectories was explored. Three tests were administered at six-month intervals among 890 children from central China. Using a person-centered approach, the study found three heterogeneous developmental trajectories for childhood depression/neuroticism and three heterogeneous joint developmental trajectories. The heterogeneity of children's development should not be overlooked when recognizing patterns of depression and neuroticism in children. A decrease in children's depression levels does not mean that they are cured, and it is possible that less detectable levels of neuroticism may slowly rise simultaneously. In addition, the relationship between different types of maltreatment and independent/joint developmental trajectories of depression and neuroticism was found. Maltreatment can cause high levels of depression and neuroticism in children, but some children can remit over time; however, there exists a proportion of children who will gradually rise from initially low levels of neuroticism.